The mirage of conciliation: Difficulties and strategies for the organization of daily routines for families with children in primary education in Galicia - Varela Crespo, Laura; Gradaílle Pernas, Rita (Education Policy Analysis Archives, 2021)
Despite the advances that have been made in terms of equality, the conciliation of work, family, and personal life continues to be one of the greatest challenges in ensuring the well-being and quality of life for all members of the household. Thus, in this study it is found that the combination of family, personal, and work schedules entails serious obstacles to daily dynamics, especially when both parents work and have children of school age; a circumstance that frequently leads them to resort to the measures promoted in the workplace to guarantee family conciliation. Matching work and school schedules with personal and family time also involves making use of other school and community resources available close to the place of residence. However, other family members continue to be the main backbone in achieving conciliation. It is concluded that the search for alternatives to the work-family conflict and the organization of daily schedules require true social co-responsibility, based on the principles of justice, equality and social equity, in order to achieve the well-being of those who make up the domestic nuclei.